2008
DOI: 10.1007/s11427-008-0036-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of yak lactate dehydrogenase B gene variants by gene cloning

Abstract: Native polyacrylamide gel electrophoresis showed that two types of lactate dehydrogenase (LDH) existed in yaks. Based on the electrophoresis characteristics of LDH isoenzymes, yak LDH variants were speculated to be the gene mutation on H subunit encoded by B gene. According to the mobility in electrophoresis, the fast-band LDH type was named LDH-Hf and the slow-band LDH type LDH-Hs. In order to reveal the gene alteration in yak LDH variants, total RNA was extracted from heart tissues of yaks with different LDH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…Based on the tetramer combination of LDH isozymes, we previously proposed that the occurrence of genetic polymorphisms of H subunit of LDH might give rise to 5 to 2 isozyme forms for LDH1 to LDH4, respectively [6]. In this study, we observed clearly the existence of multiple bands of LDH1 to LDH3 isozymes (Figure 1, lane 7).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Based on the tetramer combination of LDH isozymes, we previously proposed that the occurrence of genetic polymorphisms of H subunit of LDH might give rise to 5 to 2 isozyme forms for LDH1 to LDH4, respectively [6]. In this study, we observed clearly the existence of multiple bands of LDH1 to LDH3 isozymes (Figure 1, lane 7).…”
Section: Discussionsupporting
confidence: 60%
“…We have previously identified two phenotypes of LDH1 in Maiwa yaks (a yak breed in China) by gene cloning [6], and purified three phenotypes of LDH1 in Jiulong yaks [9]. In this study we obtained three ldhb cDNA sequences, encoding H subunits, of the three LDH1 phenotypes of Jiulong yaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As LDH subunits assemble to form tetramers, theoretically five forms of LDH1 can exist in heterogeneous yak individuals. Likewise, the proposed number of heterogeneous forms of LDH2 is four, LDH3 is three, LDH4 is two, and LDH5 is one (Zheng et al 2008). We did observe multiple bands for LDH1 to LDH3 in this study (Fig.…”
Section: Tissue Differences In Ldh and Mdh Total Activitysupporting
confidence: 64%
“…These data will assist in the evaluation of the effect of yak LDH1 variants on tissue metabolism. We have previously identified two variants of LDH1 in Maiwa yak (a yak breed in China) by gene cloning (Zheng et al 2008). In this experiment we revealed three LDH1 variants in Jiulong yak by PAGE.…”
Section: Tissue Differences In Ldh and Mdh Total Activitymentioning
confidence: 91%